KEBAHAGIAAN GURU BK USIA DEWASA MADYA DITINJAU DARI GENDER DAN WILAYAH TEMPAT TINGGAL - Nofriza, Fatma; Dewi Sukmawardhani, Chandra (EPIK: Edukasi Penerapan Ilmu Konseling, 2022)
Providing services at school requires healthy psychological conditions, one of which is feeling happy at school. The purpose of this study was to determine the differences in the happiness of counseling teachers based on the area of residence. This study uses a quantitative descriptive method with independent sample test data analysis. The research subjects were BK Kuningan and DKI Jakarta teachers with a total of 83 people, consisting of 50 female BK teachers and 43 male teachers. Meanwhile, based on the area, there are 63 teachers in Kuningan and 21 in Jakarta. The instrument used to measure authentic happiness is a modification of the Authentic Happiness Inventory (AHI). The results of independent samples test data analysis were obtained for gender with a significance of <0.05 (0.000 <0.05), so there was a difference in the happiness of counseling teachers based on gender. Whereas for independent samples test data analysis based on area of residence with a significance of > 0.05 (0.428 > 0.05), there is no difference in the happiness of counseling teachers based on the Kuningan and Jakarta areas.